2012
DOI: 10.1371/journal.pone.0029858
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility of Modified Surviving Sepsis Campaign Guidelines in a Resource-Restricted Setting Based on a Cohort Study of Severe S. Aureus Sepsis

Abstract: BackgroundThe Surviving Sepsis Campaign (SSC) guidelines describe best practice for the management of severe sepsis and septic shock in developed countries, but most deaths from sepsis occur where healthcare is not sufficiently resourced to implement them. Our objective was to define the feasibility and basis for modified guidelines in a resource-restricted setting.Methods and FindingsWe undertook a detailed assessment of sepsis management in a prospective cohort of patients with severe sepsis caused by a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…A previous single center study in this region from 2006 to 2007 reported a mortality rate of 20% at 12 weeks in hospitalized patients with non-nosocomial invasive S. aureus infection (defined as S. aureus cultured from a sterile site) 13. In a related analysis of patients with S. aureus bacteremia—including nosocomial infection—who met criteria for severe sepsis, the 28-day mortality rate was 53% 18. Together, these results underscore the significant burden of severe staphylococcal sepsis in northeast Thailand.…”
Section: Discussionmentioning
confidence: 98%
“…A previous single center study in this region from 2006 to 2007 reported a mortality rate of 20% at 12 weeks in hospitalized patients with non-nosocomial invasive S. aureus infection (defined as S. aureus cultured from a sterile site) 13. In a related analysis of patients with S. aureus bacteremia—including nosocomial infection—who met criteria for severe sepsis, the 28-day mortality rate was 53% 18. Together, these results underscore the significant burden of severe staphylococcal sepsis in northeast Thailand.…”
Section: Discussionmentioning
confidence: 98%
“…In Vietnam, the national guidance of management for emerging respiratory diseases are established to use as reference for the clinical management at all level of hospitals in the country but are not regularly updated and may lead to mismatch with international guidelines. As well, because of the considerable facility shortages seen around the world, several modified sepsis guidelines for resource-restricted settings have been recommended [33][34][35][36]. Future national guidelines and training materials need to be adapted and modified according to the reality of the resource-constraints and health system organization.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive microbiological diagnosis allows the administration of appropriate antibiotics. A prospective survey of 72 adults with severe sepsis or septic shock with S. aureus bacteremia in Thailand reported 78% patients were empirically treated with appropriate antibiotics, but after culture result, 98% were given effective antibiotic therapy [49]. In addition, as discussed above, by detecting infections such as tuberculosis or melioidosis, the necessary treatment to prevent relapse or resistance can be given.…”
Section: Availability Feasibility and Affordabilitymentioning
confidence: 99%
“…Ultrasound and X-ray are the most available and inexpensive investigations to aid the anatomical infection site, and we found low-grade evidence of both investigations showing reasonable sensitivity in abdominal perforation and melioidosis. Radiological examination was available in 86% of patients with severe sepsis and septic shock associated with S. aureus bacteremia in Thailand [49], and in 15 out of 46 cases where an anatomical site of infection was identified, appropriate source control procedures occurred, although in five further cases, the patient was deemed unfit for the appropriate surgical procedure.…”
Section: Availability Affordability and Feasibilitymentioning
confidence: 99%